Sustainability: Modern fixed and mobile networks compared across different regional structures - Gonzalo Zuloaga; Thomas Plückebaum; Gabriele Kulenkampff; Matthias Wissner (WIK Wissenschaftliches Institut für Infrastruktur und Kommunikationsdienste, 2024)
This study analyses and quantifies the energy consumption and CO2 emissions associated with operating modern telecommunications access networks, both fixed broadband (FFTH) and mobile networks (4G/5G). To quantify the environmental impacts, specific bottom-up models for the fixed and mobile access network are developed and used to endogenously determine the asset-related quantities of active network elements and their respective energy consumption. The modelling task is carried out for Germany based on household and population data at municipality level from the German Federal Institute for Research on Building and Regional Planning (BBSR), energy consumption data from the EU Code of Conduct on Energy Consumption of Broadband Communication Equipment and the CO2 emission factor for the electricity mix from the German Federal Environment Agency, in order to capture the demand for VHCN fixed and mobile access services. Furthermore, the study investigates how different settlement structures shape the environmental footprint of telecommunications networks. Based on these findings, it is analysed whether the use of mobile networks represents a sustainable strategy for the supply of rural areas in comparison to fixed network technologies. From an environmental perspective, mobile networks, especially 5G, are considered as a possible substitute for the provision of broadband access in rural areas. The analysis shows that, from an environmental perspective, FTTH access networks perform better than mobile access networks. These findings hold for any regional structure but are even more significant for rural areas. The analysis focuses on energy consumption and CO2 emissions of network operations. Deployment-related emissions and spill-over effects induced by using ICT for eco-benefits in other sectors are beyond the scope of this analysis. – – Die Studie untersucht den Energieverbrauch und die CO2 Emissionen moderner fester (FTTH) und mobiler (4G/5G) Telekommunikationszugangsnetze in Deutschland und überprüft damit die Umweltauswirkungen des Telekommunikationssektors aus dem Netzbetrieb. Zur Quantifizierung werden zwei Bottom-Up Kostenmodelle (für Fest- und Mobilnetz) entwickelt, die die benötigten Netzwerkelements und deren Energiebedarf bestimmen. Die Netze sind für VHCN-Verkehr dimensioniert. Emissionen aus dem Netzausbau werden wegen geringer Relevanz vernachlässigt. Die Studie bestimmt zudem die regionalen Auswirkungen unterschiedlicher Besiedlungsstrukturen auf diese Infrastrukturen und deren Energieverbrauch und erarbeitet ein nuanciertes Verständnis der wechselseitigen Abhängigkeiten und Auswirkungen. Zum Abschluss bewertet die Studie das Potential mobiler Anschlussnetze aus Nachhaltigkeitsgesichtspunkten, FTTH Anschlussnetze substituieren zu können, insbesondere in ländlichen und dünn besiedelten Regionen. FFTH Anschlussnetze sehen sich z.T. vor großen Herausforderung im ländlichen Raum bzgl. der Kosten zum Zugang entlegender Häuser, für die 5G ein Ersatz sein könnte. Dazu werden die betrieblichen CO2 Emissionen beider Anschlusstechniken miteinander verglichen. Darüber hinaus gehende indirekte Auswirkung aus der Nutzung von IKT-Tools zur Energieeinsparung in anderen Sektoren werden nicht betrachtet, weil sie von der Wahl der Anschlussnetze nicht berührt werden. Im Ergebnis sind die FTTH Anschlussnetze aus der ökologischen Perspektive über alle Regioklassen deutlich besser, und dies insbesondere in den dünn besiedelten ruralen Bereichen.
Keywords: 330